Pediatric gastroenterology and nutrition : a practically painless review - Houser, Christine M. (Springer New York, 2014)
Often, information in review books can raise as many questions as it answers. This interferes with the study process, because the learner must either look up additional information or skip ahead without truly comprehending what he or she has read. As an alternative, Pediatric Gastroenterology and Nutrition: A Practically Painless Review presents bite-size chunks of information that can be read and processed rapidly, helping learners to stay active while studying and to pick up new information the first time they read it. This book's question and answer format allows for self-testing or study with a partner or a group. The format also facilitates dipping into the book during a few minutes of downtime at the hospital or office. Pediatric Gastroenterology and Nutrition: A Practically Painless Review is a quick and easy way to master these tricky topics and is suitable for those studying for the pediatric board exam, practicing physicians brushing up their skills and any busy clinician who wants to learn more about these topics while on the go.